PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI KECAMATAN DI KECAMATAN GIRIAN KOTA BITUNG - ADITYA, NUGRAHENI; DENGO, SALMIN; PALAR, NOVIE (Sam Ratulangi University, 2019)
The work environment is one of the factors that affect the performance of employees. An employee whoworks a work surroundings that support that an employee to work optimally will produce a goodperformance. However, if instead when an employee is on a work environment that does not support suchas lack of facilities, unsafe workplaces, noisy and hot then it is certain performance results employees willbe low. This research method using quantitative research i.e. research which analysed the data instatistics with the aim to find out whether the work environment affects employee performance. Datacollection is done by way of spreading the now at 63 employees then the data processed using the SPSSversion application 22. Work environment positive and significant effect on performance clerk GirianSubdistrict. Which means that the better work environment physical and non physical then theperformance of employees. The work environment has a fairly strong correlation and significantly to thedevelopment of the performance of government employees Girian Subdistrict. Suggestions in this study isthe importance of improving the atmosphere of the working environment is good and conducive in raisingemployee productivity and expected the Government Town of Bitung can maintain and improve thephysical work environment and non-physical.Keywords: work environment, performance , Employees.